Role of the Agriculture on Economic Growth in Nepal: An Explanatory Research - Lamichhane, Basu Dev; Chalise, Mahananda; Karki, Tej Bahadur; Neupane, Dasarath (NPRC Journal of Multidisciplinary Research, 2026)
Background: Still, the agricultural sector remains central as the driving force for enhancing GDP and job creation. The research investigates how agriculture functions as an economic driver, creating direct connections to productivity, rural development, and structural economic changes.Objective: The study aims at assessing the contribution of the agriculture sector to the country's economic growth. Recently, the Nepalese agricultural sector has faced several challenges, including low investment, limited adoption of technology, infrastructural problems, and marketing challenges.Research design: The study employs descriptive and analytical methods that are convenient to illustrate through tables, figures, and charts while presenting the data. On this basis, the secondary data from the Nepal Rastra Bank and the World Bank Development Indicators have been collected.Findings: The research manifested that the agricultural sector plays a vital role in Nepal’s GDP and job creation, thus the agricultural sector is a crucial element for the national economy. Therefore, agriculture not only sustains a large segment of the population by providing employment and food security but also supports the livelihoods of rural smallholders.Conclusion: The study’s central finding is that investments in modern agricultural tools further help to improve irrigation systems and value chain mechanisms of agro-processing industries established in different places within the country. The systems and mechanisms mentioned in the research results demonstrate that the agricultural sector significantly enhances the national GDP.Novelty: The study is useful in the field of agricultural sectors, outlining some dimensions of economic growth through employment that alleviates poverty and fosters GDP. Implication: The findings of this study can be a benchmark for GDP growth. It will be useful for policymakers, regulators, economists, scholars, academicians, development leaders, private sector, and other stakeholders who are striving for economic growth and policy formations in their respective fields or industries.